The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/2016ea000240
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Upward Directed Charged Particle Fluxes in the Mars Science Laboratory Radiation Assessment Detector

Abstract: The Mars Science Laboratory rover Curiosity, operating on the surface of Mars, is exposed to radiation fluxes from above and below. Galactic Cosmic Rays travel through the Martian atmosphere, producing a modified spectrum consisting of both primary and secondary particles at ground level. These particles produce an upward directed secondary particle spectrum as they interact with the Martian soil. Here we develop a method to distinguish the upward and downward directed particle fluxes in the Radiation Assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In the current model setup, we use the atmosphere profile from MCD above the ground at the location of Gale Crater, which is the landing site of the Curiosity rover. More detailed descriptions of features of the MCD implemented in the model used here can be found in Guo JN et al (2018a, 2019a and Appel et al (2018). Particularly relevant to the current study is that the GEANT4/PLAN-ETOCOSMICS model has been shown to be able to predict reliably the surface charged particle spectra and dose rates of the GCR-induced surface radiation (Matthiä et al, 2016) as actually measured by RAD.…”
Section: The Martian Particle Transport Modelmentioning
confidence: 74%
“…In the current model setup, we use the atmosphere profile from MCD above the ground at the location of Gale Crater, which is the landing site of the Curiosity rover. More detailed descriptions of features of the MCD implemented in the model used here can be found in Guo JN et al (2018a, 2019a and Appel et al (2018). Particularly relevant to the current study is that the GEANT4/PLAN-ETOCOSMICS model has been shown to be able to predict reliably the surface charged particle spectra and dose rates of the GCR-induced surface radiation (Matthiä et al, 2016) as actually measured by RAD.…”
Section: The Martian Particle Transport Modelmentioning
confidence: 74%
“…Appel et al (2018) have studied the charged protons detected in RAD's vertical telescope cone (with a half angle of 18°) and found a 10% ratio of the upward to downward flux of 100-200 MeV protons. This ratio is different from what we obtain here mainly for two reasons: (1) dose is contributed by all particles over a wide energy range and cannot be represented solely by protons in this energy range and (2) downward particles within the semi-vertical cone used in Appel et al (2018) traverse through a much thinner atmosphere than those coming from more horizontal directions so that the downward flux/dose ratio in this cone is different from the averaged downward value.…”
Section: Discussionmentioning
confidence: 99%
“…While any difference between the fraction of sky obscured by Venus and the fractional decrease in GCR count rate is small enough to potentially be a result of instrumental uncertainty, it is possible that some of the discrepancy could be due to primary GCRs interacting with the atmosphere and surface of Venus, leading to the production of secondary particles (i.e., albedo particles) which are then detected by HET. Such albedo particles have been measured at Mars with the RAD instrument on Mars Science Laboratory (Appel et al 2018) and at the Moon with the CRaTER (Schwadron et al 2016) andLND (Wimmer-Schweingruber et al 2020) instruments. Measured fluxes are on the order of 10% of the downward flux in the case of Mars in the energy range that can be measured by the RAD instrument (Appel et al 2018).…”
Section: Obstruction Of Galactic Cosmic Rays By Venusmentioning
confidence: 99%
“…Such albedo particles have been measured at Mars with the RAD instrument on Mars Science Laboratory (Appel et al 2018) and at the Moon with the CRaTER (Schwadron et al 2016) andLND (Wimmer-Schweingruber et al 2020) instruments. Measured fluxes are on the order of 10% of the downward flux in the case of Mars in the energy range that can be measured by the RAD instrument (Appel et al 2018). If these albedo particles are being produced at Venus, it would seem that their flux at~2 R V is small.…”
Section: Obstruction Of Galactic Cosmic Rays By Venusmentioning
confidence: 99%